Current knowledge about the impact of microgravity on the proteome. (2nd January 2019) - Strauch, Sebastian M.; Grimm, Daniela; Corydon, Thomas J.; Krüger, Marcus; Bauer, Johann; Lebert, Michael; Wise, Petra; Infanger, Manfred; Richter, Peter
ABSTRACT: Introduction : Microgravity (µ g ) is an extreme stressor for plants, animals, and humans and influences biological systems. Humans in space experience various health problems during and after a long-term stay in orbit. Various studies have demonstrated structural alterations and molecular biological changes within the cellular milieu of plants, bacteria, microorganisms, animals, and cells. These data were obtained by proteomics investigations applied in gravitational biology to elucidate changes in the proteome occurring when cells or organisms were exposed to real µ g (r-µ g ) and simulated µ g (s-µ g ). Areas covered : In this review, we summarize the current knowledge about the impact of µ g on the proteome in plants, animals, and human cells. The literature suggests that µ g impacts the proteome and thus various biological processes such as angiogenesis, apoptosis, cell adhesion, cytoskeleton, extracellular matrix proteins, migration, proliferation, stress response, and signal transduction. The changes in cellular function depend on the respective cell type. Expert commentary : This data is important for the topics of gravitational biology, tissue engineering, cancer research, and translational regenerative medicine. Moreover, it may provide new ideas for countermeasures to protect the health of future space travelers.